Subsurface oxygen minima regulated by remineralization and bottom flushing along 123°E in the inner East China Sea - Wang, Bin; Chen, Jianfang; Jin, Haiyan; Li, Dewang; Gao, Shengquan; Tian, Shichao; Sun, Lin; Zhang, Haizhou; Li, Linwei (Frontiers in Marine Science, 2023)
The summer hypoxia off the Changjiang Estuary is one of the largest coastal hypoxic systems in the world and has displayed spatial heterogeneity in recent years. Based on observation data in the summer of 2014, hypoxia was identified both in the bottom and mid-layers. Except for the typical bottom hypoxia in the submarine canyon, the subsurface oxygen minima (SOM) were captured in the mid-layer of 10 15 m, with lower dissolved oxygen in the mid-layer than at the bottom (30–50 m). This SOM phenomenon was located in the lower boundary of the pycnocline and above the Taiwan warm current (TWC) and Kuroshio subsurface water (KSSW). Due to the southern expansion of Changjiang diluted water (CDW), a high phytoplankton biomass (the maximum chlorophyll a of 25 μg L−1, pH of 8.6, and DO of 11 mg L−1) band occupied the surface area along 123°E. By analyzing the 24-h continuous observation and high-resolution profile data, we revealed that the subsurface oxygen minima were predominantly controlled by remineralization and bottom-flushing effects. Fast local consumption occurred near the pycnocline layer, while the lateral transport of oxygen-rich ambient water replenished the bottom oxygen deficit from south to north. We summarize and contextualize three hot spots of hypoxia into a conceptual diagram and emphasize the influences of advection, mixing, and respiration on their location and severity. Overall, compared with the discussion about the low DO background of TWC/KSSW, this research highlights the flushing effects of TWC/KSSW that will reshape the hypoxia structure and alleviate the hypoxia severity in the south hypoxia area off the Changjiang Estuary.